2015
DOI: 10.4097/kjae.2015.68.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the rate of successful endotracheal intubation between the "sniffing" and "ramped" positions in patients with an expected difficult intubation: a prospective randomized study

Abstract: BackgroundOptimal head and neck positioning and clinical experience are important factors for successful endotracheal intubation in patients with a difficult airway. This study aimed to investigate the rate of successful endotracheal intubation between the sniffing and ramped positions in patients with an expected difficult intubation.MethodsThe study included 204 patients with an expected difficult intubation (airway difficulty score ≥ 8) based on the preoperative airway assessment. The patients were randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 18 publications
2
41
0
1
Order By: Relevance
“…One randomized controlled trial of ramped versus sniffing head position during urgent intubations in the ICU found that ramping worsened the Cormack-Lehane grade view of the airway, while a similar study in an operating room population showed significantly better laryngeal views when patients were ramped. 20,21 Despite these mixed data, more than one-quarter of all patients in our study were placed in a ramped position. This parallels the percentage of patients listed as being either obese or morbidly obese.…”
Section: Discussionmentioning
confidence: 84%
“…One randomized controlled trial of ramped versus sniffing head position during urgent intubations in the ICU found that ramping worsened the Cormack-Lehane grade view of the airway, while a similar study in an operating room population showed significantly better laryngeal views when patients were ramped. 20,21 Despite these mixed data, more than one-quarter of all patients in our study were placed in a ramped position. This parallels the percentage of patients listed as being either obese or morbidly obese.…”
Section: Discussionmentioning
confidence: 84%
“…This is also the aim in 'ramping' which has an established role in obese patients. [ 8 9 ] This practice is however not routine for non-obese patients. The aim of the present study was to compare a fixed height obtained by routinely used ring versus a customised height by addition of sheets (for horizontal alignment of EAM and sternum) to achieve head elevation for tracheal intubation in terms of glottis visualisation and time taken for intubation.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the studies which compared the ramped position and the sniffing position showed relatively conflicting results. Ramped position was proved superior to sniffing position in both obese, non-obese populations [11]; and in patients with expected difficult intubation [12]. Semler et al had, surprisingly, reported different results which favored the sniffing position over the ramped position in 260 critically ill patients [6].…”
Section: Discussionmentioning
confidence: 99%